Going underground : the meanings of death and burial for minority groups in Israel - Shay, Talia (Archaeopress, 2021)
"Going Underground: The Meanings of Death and Burial for Minority Groups in Israel is about the attitudes towards death and burial in contemporary society. It provides information on the attitudes of several minority groups living in Israel today, including four communities of Russian Jews, an ultra-religious Jewish community and a Palestinian-Christian community. 'Going Underground' has a double meaning: it refers to the actions taken by archaeologists to inquire about the past and present and involves digging and recording. Second, it considers the challenges and protests launched by the groups of immigrants and minorities mentioned in the book, against state-control over death" -- Back cover.